2017
DOI: 10.1080/09712119.2017.1411267
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary Bacillus subtilis supplementation on the growth performance, blood profile, nutrient retention, and caecal microflora in broiler chickens

Abstract: The objective of this study was to evaluate the effects of the B. subtilis RX7 and B. subtilis C14 on the growth performance, blood profiles, nutrient retention, and caecal microflora of broiler chickens. A total of 288, 1-d-old Ross 308 male broilers were assigned to one of four dietary treatment groups for 35 days; the negative control (NC; basal diet with no antibiotic or B. subtilis), positive control (PC; NC + 40 ppm avilamycin), T1 (NC + 0.1% B. subtilis RX7 1.0×109 cfu/g), and T2 (NC + 0.1% B. subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…According to the concentration level of LAB, a notable effect (p<0.05) on body weight occurred when ducks were administered LAB starting at 10 7 cfu/ml and above compared to control treatment. The heightened body weight in this study was in line with the other studies (Shokryazdan et al, 2017;Abdel-Hafeez et al, 2017;Park et al, 2018), who stated that supplementation of probiotics was able to increase body weight gain and gain a greater body weight compared to the non-probiotic treatment in the whole experiment. These findings are also in agreement with Mohammadi Gheisar et al 2016and Lan et al (2017) that dietary LAB probiotics containing Enterococcus faecium were able to improve the live body weight of chickens compared with the control treatment.…”
Section: Live Body Weight Of Pegagan Duckssupporting
confidence: 91%
See 2 more Smart Citations
“…According to the concentration level of LAB, a notable effect (p<0.05) on body weight occurred when ducks were administered LAB starting at 10 7 cfu/ml and above compared to control treatment. The heightened body weight in this study was in line with the other studies (Shokryazdan et al, 2017;Abdel-Hafeez et al, 2017;Park et al, 2018), who stated that supplementation of probiotics was able to increase body weight gain and gain a greater body weight compared to the non-probiotic treatment in the whole experiment. These findings are also in agreement with Mohammadi Gheisar et al 2016and Lan et al (2017) that dietary LAB probiotics containing Enterococcus faecium were able to improve the live body weight of chickens compared with the control treatment.…”
Section: Live Body Weight Of Pegagan Duckssupporting
confidence: 91%
“…The unmarked hematological parameters in this study are in line with other studies related to probiotic supplementation. The numbers of RBC and WBC in birds was reported not to be significantly increased by the administration of various probiotic strains, such as Bacillus subtilis RX7 and B2A (Park and Kim, 2014), E. faecium (Lan et al, 2017), and B. subtilis RX7 and C14 (Park et al, 2018), with the amounts of 2.00-2.01 (10 6 /µL) and 27.7-28.5 (10 3 /µL), 2.11-2.46 (10 6 /µL) and 19.9-20.8 (10 3 /µL), and 2.17-2.22 (10 6 /µL) and 29.2-31.0 (10 3 /µL), respectively. Those RBC and WBC values appear to be lower than that of this study, namely 4.20-4.50 (10 6 / µL) and 26.04-29.00 (10 3 /µL).…”
Section: Blood Hematological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with previous reports showing that probiotics do not induce significant changes in the hematological values of the broilers. ( Park and Kim 2014 ; Gutierrez and Corredor 2017 ; Park et al., 2018 ). Nevertheless, normal blood counts do not exclude the possibility of altered immune status or stress induced by environmental factors ( Avilez et al., 2014 ; Diaz et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that Bacillus subtilis alone or combined with other bacteria can be used as growth promotors or immunomodulatory factors to increase energy retention, weight gain, and feed conversion in broiler chickens [20,21]. One of the mechanisms of its effects is to enhance feed digestion and nutrient resorption in the gastrointestinal tract (GIT) [22,23], leading to positive effects on preventing bone mass loss [24] by improving bone density and mineral content such as Ca and phosphorus (P) [24][25][26].…”
Section: Introductionmentioning
confidence: 99%